EFEKTIVITAS POINT OF PURCHASE DALAM MENINGKATKAN IMPULSE BUYING PADA PERITEL DI SURABAYA - SANYOGO, MELISA CANCERINA (Universitas Katolik Widya Mandala Surabaya, 2013)
Tendency impulse buying is buying behavior lively trend in hypermarkets and supermarkets. In this condition the promotion sales (sales promotion) is one of the elements of the promotion mix to be very important. Variegated form of sales promotion. The best known was a POP or point-of-purchase. POP covers all visual forms created by brand owners, ranging from the installation of hanging display, advertising on the floor until the product placement or sequence of interest. Therefore authors interested in writing more about how point of purchase can increase the effectiveness of impulse buying on the retailers in Surabaya. Point of Purchase (POP) can be divided into three kinds, namely: 1) permanent POP; 2) POP contingent; and 3) Media in store. POP due to the desire to achieve: 1) results for producers; 2) services for the Retailer; and 3) Value for the consumer. POP has the greatest influence on impulse buying compared different types of promotion methods. Reason in-store advertisement had the greatest influence is because of this promotion made available where purchase decisions made.